2011
DOI: 10.1016/j.febslet.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of the metal-ion in the IPM-assisted domain closure of 3-isopropylmalate dehydrogenase

Abstract: Edited by Stuart FergusonKeywords: Domain movement Substrate and metal-effect 3-Isopropylmalate dehydrogenase Small-angle X-ray scattering a b s t r a c t X-ray structures of 3-isopropylmalate dehydrogenase (IPMDH) do not provide sufficient information on the role of the metal-ion in the metal-IPM assisted domain closure. Here solution studies were carried out to test its importance. Small-angle X-ray scattering (SAXS) experiments with the Thermus thermophilus enzyme (complexes with single substrates) have rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The K d values of IPM binding were determined by fitting the dependences of the rate constants of FRET signal formation and the FRET amplitudes on the concentration of IPM to a single binding hyperbola. The K d values obtained from the whole FRET signal (A 1 + A 2 ) agree well with the value determined earlier [19]. ND, not determined.…”
Section: Itc Binding Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…The K d values of IPM binding were determined by fitting the dependences of the rate constants of FRET signal formation and the FRET amplitudes on the concentration of IPM to a single binding hyperbola. The K d values obtained from the whole FRET signal (A 1 + A 2 ) agree well with the value determined earlier [19]. ND, not determined.…”
Section: Itc Binding Studiessupporting
confidence: 88%
“…Control kinetic experiments with EDTA indicated that EDTA does not compete with binding of IPM; that is, inhibition by EDTA is solely attributable to withdrawal of the metal ion from the IPMDH active site .…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies with the wild‐type Tt ‐IPMDH we clearly detected domain closure in the complex with Mn 2+ and IPM [19]. This experiment was repeated with the mutant E270A that also binds the substrate MnIPM.…”
Section: Resultsmentioning
confidence: 70%
“…The radii of gyration and the scattering patterns from the crystallographic models of wild‐type apo Tt ‐IPMDH (pdb: 2Y3Z) and its substrate complex with Mn 2+ , IPM and NADH (pdb: 4F7I) were computed using the program CRYSOL [18]. The program OLIGOMER [15] was used to calculate the ratio of open‐ and closed‐form species present in Tt ‐IPMDH solutions as described in [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation